Heparanase Expression in Circulating Lymphocytes of Breast Cancer Patients Depends on the Presence of the Primary Tumor and/or Systemic Metastasis - Theodoro, Thérése Rachell; de Matos, Leandro Luongo; Lambiasi Sant Anna, Aleksandra Vanessa; Fonseca, Fernando Luiz Affonso; Semedo, Patrícia; Martins, Lourdes Conceição; Nader, Helena Bonciani; Del Giglio, Auro; da Silva Pinhal, Maria Aparecida (Neoplasia (New York, N.Y.), 2007)
Heparanase is an endo-β-glucuronidase that is capable of degrading heparan sulfate chains of proteoglycans, generating a variety of bioactive molecules such as growth factors and chemotactic and angiogenic agents. The expression of heparanase was investigated in the peripheral blood mononuclear cell fraction (PBMC) of 30 patients with breast cancer and 20 healthy control women by reverse transcription—polymerase chain reaction (RT-PCR) and immunocytochemistry. PBMC samples from all breast cancer patients at study entry showed the expression of heparanase, whereas no expression was observed for healthy women. Immunocytochemistry analysis demonstrated that heparanase was expressed in lymphocytes of breast cancer PBMC. Throughout follow-up, heparanase expression by RTPCR decreased significantly after surgery in patients treated with neoadjuvant chemotherapy (P = .002) and after tamoxifen treatment (P = .040), whereas it increased significantly with the advent of systemic metastasis (P = .027). In vitro, either serum from breast cancer patients or a medium originated from coculture experiments of MCF-7 cells and lymphocytes from healthy women stimulated heparanase expression in normal lymphocytes. The results suggest that there is a tumor-inducing effect on heparanase expression by lymphocytes present in the PBMCs of breast cancer patients, which depends, in turn, on the interaction between a tumor and normal lymphocytes.